2014
DOI: 10.1890/es13-00238.1
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing winter habitat quality for greater sage‐grouse in a landscape influenced by energy development

Abstract: Prioritizing habitats that provide the best options for the persistence of sensitive species in human‐modified landscapes is a critical concern for conservation. Linking occurrence and fitness parameters across multiple spatial scales provides an approach to address habitat prioritization for species of concern in disturbed habitats. To demonstrate the usefulness of this approach, we generated resource selection and survival risk models as a framework to quantify habitat value for wintering female greater sage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 82 publications
2
57
0
Order By: Relevance
“…Sage‐grouse selected landscapes that were less rugged with warmer aspects dominated by sagebrush. These findings were generally consistent with previous winter sage‐grouse research (Carpenter et al ; Smith et al , ; Holloran et al ; Walker et al ). Sage‐grouse also selected winter habitats closer to leks and in areas with greater breeding densities (as indexed by male lek counts) within 11.1 km of known leks.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Sage‐grouse selected landscapes that were less rugged with warmer aspects dominated by sagebrush. These findings were generally consistent with previous winter sage‐grouse research (Carpenter et al ; Smith et al , ; Holloran et al ; Walker et al ). Sage‐grouse also selected winter habitats closer to leks and in areas with greater breeding densities (as indexed by male lek counts) within 11.1 km of known leks.…”
Section: Discussionsupporting
confidence: 91%
“…Sage‐grouse are a partially migratory species with many individuals within populations using spatially distinct breeding and winter habitats (Connelly et al , Dinkins et al , Pratt et al ). During winter, sage‐grouse generally require large expanses of sagebrush above snow in flatter terrain with few anthropogenic features (Doherty et al ; Carpenter et al ; Dzialak et al ; Smith et al , ; Holloran et al ). The Wyoming Sage‐grouse Executive Order recognized a need to identify areas where sage‐grouse exhibit concentrated winter use (winter concentration areas [WCAs]) because these areas may not have been adequately protected with the Core Area Strategy's focus on breeding habitat.…”
mentioning
confidence: 99%
“…Sage-grouse research using presence-absence data has consistently revealed disproportionately low use of habitat associated with energy infrastructure (Aldridge and Boyce 2007, Naugle et al 2011, Hess and Beck 2012, Smith et al 2014). Therefore, it is important to consider our findings in the context of female sage-grouse choices for nest placement.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we removed aspen ( Populus tremuloides ) and forest because models did not converge due to the lack of these variables in the presence buffers in all seasons. Thus, the vegetation categories we used in model development were irrigated agriculture, sagebrush, grassland, sagebrush/grassland, and riparian, which have all been shown to be important predictors of GRSG habitat in previous studies (S1 Appendix; [15, 19, 2628]). We also updated the irrigated agriculture vegetation class from the basinwide layer using the Colorado Division of Water Resources District 47 irrigated agriculture shapefile from 2011 [29].…”
Section: Methodsmentioning
confidence: 99%
“…Previous research examining the effects of energy development on habitat use suggests that GRSG populations are negatively affected by energy development activities, especially those that degrade important sagebrush habitat [1012]. This often results in a decrease in available habitat or the avoidance of critical seasonal habitat [13–15]. Most of these studies have been conducted in areas where energy development already exists at high levels of development.…”
Section: Introductionmentioning
confidence: 99%